The Effect of Service Quality and Trust on Customer Loyalty with Satisfaction as an Intervening Variable in Three Star Hotels, Palembang - Tania, Luthfia Renalda; Rahmanita, Myrza; Ingkadijaya, Rahmat; Karo, Pelliyezer Karo (Journal of Management and Administration Provision, 2024)
This research aims to analyze the direct and indirect influence of the variables Service Quality, Trust, Satisfaction and Customer Loyalty. The method used in this research is a quantitative method with primary andsecondary data collection techniques, including observation, questionnaires and literature study. The number of respondents involved in this research was 115 people, and data collection was carried out using instruments that focused on the variables studied. Data analysis was carried out using Smart-PLS software. Based on the results showed that satisfaction has a significant influence on customer loyalty Apart from that, trust also has a significant influence on satisfaction, and the influence of trust on customer loyalty through satisfaction shows significant results. Trust and satisfaction are important factors that influence customer loyalty in three-star hotels in Palembang City. The results of this research also show that the other four variables, namely the direct influence of service quality on customer loyalty, as well as the influence of service quality on trust and satisfaction, have an insignificant influence. Therefore, to increase customer loyalty to three-star hotels in Palembang, it is necessary to look for other factors that have a stronger and more significant influence.